2015
DOI: 10.1007/s10120-015-0558-0
|View full text |Cite
|
Sign up to set email alerts
|

Atrophic gastritis and enlarged gastric folds diagnosed by double-contrast upper gastrointestinal barium X-ray radiography are useful to predict future gastric cancer development based on the 3-year prospective observation

Abstract: Of the 6433 subjects, 1936 (30.1 %) had atrophic gastritis and 1253 (19.5 %) had enlarged gastric folds. During the 3-year prospective observational follow-up, gastric cancer developed in seven subjects, six of whom (85.7 %) had atrophic gastritis with H. pylori infection and five of whom (71.4 %) had enlarged gastric folds with H. pylori infection. The Kaplan-Meier method with log-rank testing revealed that both UGI-XR-based atrophic gastritis (p = 0.0011) and enlarged gastric folds (p = 0.0003) are significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The greatest risk of follow-up observation without UGI-ES is to erroneously diagnose protruded early gastric cancers as nonmalignant gastric polyps, but our results indicate such misdiagnoses are quite rare. Nowadays, it has been gradually accepted that UGI-XR can detect not only gastric cancer but also premalignant atrophic/hypertrophic gastritis [4,25,30,32]. Our recent report demonstrated that UGI-XR can diagnose chronic H. pylori infection with very high accuracy (97.8 %; 1638 of 1674 subjects) [5].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The greatest risk of follow-up observation without UGI-ES is to erroneously diagnose protruded early gastric cancers as nonmalignant gastric polyps, but our results indicate such misdiagnoses are quite rare. Nowadays, it has been gradually accepted that UGI-XR can detect not only gastric cancer but also premalignant atrophic/hypertrophic gastritis [4,25,30,32]. Our recent report demonstrated that UGI-XR can diagnose chronic H. pylori infection with very high accuracy (97.8 %; 1638 of 1674 subjects) [5].…”
Section: Discussionmentioning
confidence: 94%
“…Synthetic diagnoses from the judgments of these three specialists were used for the analyses. UGI-XR-based atrophic gastritis was classified into four types according to our recent reports as follows [5,25,30]: no atrophic gastric mucosa (type A), mild atrophic gastritis (type B), moderate atrophic gastritis (type C), and severe atrophic gastritis (type D).…”
Section: Diagnosis Of Gastric Polyps and Atrophic Gastritis By Upper mentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan and Korea, barium swallow continues to be one of the main choices for mass screening of gastric cancer; approximately 4,000,000 individuals undergo barium swallow testing annually In Japan and approximately 1,000,000 individuals undergo annual barium studies in Korea [14, 18, 19]. A serious drawback is low uptake of the target population; fear for radiation exposure (0.6 mSv), swallowing problems with the use of unpleasant barium meal, accidental fall during the examination and constipation (6%) causing rare but more serious complications such as intestinal obstruction or diverticulitis after examination may account for the reasons for this low uptake [1].…”
Section: Discussionmentioning
confidence: 99%
“…found that the risk of gastric cancer was 35.5‐fold higher in cases with a fold width of at least 7 mm than in those with a fold width of 4 mm or less in the gastric corpus and pointed out that the fold width in the gastric corpus was a risk factor for undifferentiated gastric cancer occurring in the gastric corpus. Yamamichi et al 13 . also found the occurrence of five cases of gastric cancer in 3‐year prospective observation of 1253 patients with enlarged fold gastritis and reported that enlarged fold was a predictor of gastric cancer.…”
Section: [V] Risk Stratification After Endoscopic Examinationmentioning
confidence: 94%